Social media use and academic performance among college students: the chain mediating roles of social anxiety and fear of missing out and the moderating effect of teacher-student relationship - Gong, Zhuliu; Guo, Yi; Tan, Jinghao (Frontiers in Psychology, 2025)
ObjectiveTo explore the mechanisms by which social media use affects academic performance among college students, examining the chain mediation effects of social anxiety and fear of missing out (FoMO), as well as the moderating role of teacher-student relationships.MethodsUsing stratified cluster sampling, questionnaire data were collected from 3,716 Chinese undergraduate students aged 18–24. The questionnaires measured social media usage frequency, social anxiety, FoMO, teacher-student relationships, and academic performance. Scale reliability and validity were first examined through confirmatory factor analysis, followed by structural equation modeling to assess chain mediation effects. The moderating effect of teacher-student relationships was tested using the PROCESS Model 14 framework.ResultsSocial media use had a significant negative direct effect on college students’ academic performance. Social anxiety and FoMO served as significant mediators in this relationship. Teacher-student relationships significantly moderated the negative effect of FoMO on academic performance.ConclusionHigh-frequency social media use among college students undermines academic performance through an emotional pathway whereby social anxiety leads to increased FoMO. Strong teacher-student relationships can function as an emotional regulatory mechanism, significantly reducing this adverse impact.